Interpersonal interactions in the mobile-game environment of physical education - Fokin A.M. (Theory and Practice of Physical Culture, 2025)
Objective of the study is to model a mobile gaming environment for physical education based on interpersonal interaction between participants in the process of communication. Methods and structure of the study. 88 students majoring in education, aged 19.2±0.5 years, were involved in the scientific experiment as part of an experimental and control group in the process of physical education based on the modelling of team game situations involving the need for interaction to achieve a team result. Results and conclusions. It has been established that the formation of students’ communication competence for its subsequent implementation in the social sphere is possible through the means of a mobile game environment of physical education. Constant communication between players in a mobile game environment plays a central role in coordinating game actions.